KOMUNIKASI DAKWAH UNTUK KEADILAN: PESAN DAKWAH TERHADAP KRISIS KEMANUSIAAN PALESTINA - Muhammad Ridwan; Zenal Arifin (Mumtaz: Jurnal Studi Al-Quran dan Keislaman, 2025)
Israel's military aggression in the Gaza Strip following the ceasefire on January 19, 2025, has triggered a severe humanitarian crisis, resulting in numerous casualties, infrastructure destruction, and disruption of humanitarian aid distribution. Despite this, the international response—including from the United Nations and major powers—has not demonstrated concrete steps toward upholding justice. Existing studies on Islamic preaching (dakwah) have largely focused on spiritual, ethical, and local cultural aspects, while paying insufficient attention to dakwah's role in addressing global structural and political issues, such as the Palestinian conflict. This gap highlights the need for contextual research on dakwah grounded in the values of social justice and human rights. This article proposes a critical approach to dakwah as a form of communication for justice, emphasizing Islamic values of defending the oppressed (al-mustadh'afin), universal humanity, and the role of preachers (da'i) as moral agents shaping public opinion and global solidarity. Employing a qualitative method, this study analyzes literature and discourse from dakwah materials, scholars’ statements, and digital narratives on social media advocating for justice in Palestine. The findings reveal that dakwah communication based on justice and solidarity can awaken the collective consciousness of the Muslim community and intensify moral pressure on international institutions. The innovation of this study lies in strengthening dakwah as a justice-oriented communication model that integrates prophetic principles with public moral communication theory in the context of global humanitarian crises.